The Transformation of Blame: “Religious Thought” and the Genealogy of Scientific Explanation - Thomson, Cameron M (Religious Studies and Theology, 2010)
This essay discusses Donald Wiebe’s account of the relationship between “religious thought” and the mode of thought that he thinks typical of objective science and rational theology. First I present what I take to be Wiebe’s position. Then, drawing on René Girard’s fundamental anthropology and Michael Tomasello’s cultural-psychological work on joint attention, I offer a critique and articulate an alternative approach. I argue that the dichotomy between ostensibly objective modern scientific thought, on the one hand, and religious thought, on the other, is not an internal structural one, but concerns the radically differing value for social order accruing to otherwise commensurate modes of intersubjective attention to objects in a shared environment. I argue that the class of procedures aiming at relatively disinterested, nonagentic explanation is genetically related to the class of relatively parochial, affect-laden acts of blaming, a class that includes ex post facto (mythological) rationalizations of those proto-human reactions that engendered archaic ritual practices and systems of interdiction in the first place. The transition from religious thought to science, I conclude, is not a dichotomy in “kinds” of thought, as Wiebe argues, but arises with the historical emergence of a novel human potential for empathy and the concomitant erosion of the individual’s susceptibility, in the context of collective crises, to persuasion framed in terms of blame.